Mutations in the autoregulatory domain of β‐tubulin 4a cause hereditary dystonia. Issue 4 (19th February 2013) - Hersheson, Joshua; Mencacci, Niccolo E.; Davis, Mary; MacDonald, Nicola; Trabzuni, Daniah; Ryten, Mina; Pittman, Alan; Paudel, Reema; Kara, Eleanna; Fawcett, Katherine; Plagnol, Vincent; Bhatia, Kailash P.; et al.
<x xml:space="preserve">Abstract</x> Dystonia type 4 (DYT4) was first described in a large family from Heacham in Norfolk with an autosomal dominantly inherited whispering dysphonia, generalized dystonia, and a characteristic hobby horse ataxic gait. We carried out a genetic linkage analysis in the extended DYT4 family that spanned 7 generations from England and Australia, revealing a single LOD score peak of 6.33 on chromosome 19p13.12‐13. Exome sequencing in 2 cousins identified a single cosegregating mutation (p.R2G) in the β‐tubulin 4a (TUBB4a) gene that was absent in a large number of controls. The mutation is highly conserved in the β‐tubulin autoregulatory MREI (methionine–arginine–glutamic acid–isoleucine) domain, highly expressed in the central nervous system, and extensive in vitro work has previously demonstrated that substitutions at residue 2, specifically R2G, disrupt the autoregulatory capability of the wild‐type β‐tubulin peptide, affirming the role of the cytoskeleton in dystonia pathogenesis. Ann Neurol 2013;73:546–553